Infective endocarditis - maybe yes, maybe no: Case report - Ivanović Branislava; Tadić Marijana; Orbović Bojana; Petrović Milan (Srpski Arhiv za Celokupno Lekarstvo, 2013)
Introduction. Infective endocarditis (IE) is a rare disease which manifests in different ways. Case Outline. We are presenting a female patient who was suspected of IE based on the presence of fever, accelerated erythrocyte sedimentation rate, increased levels of C-reactive protein and echocardiographic findings of filamentous structures on the aortic valve which were assumed to be vegetation. Because of the well-known fact that in the pre-antibiotic era IE was almost always a fatal disease, empirical antibiotic therapy was conducted despite the absence of clear criteria for IE and it resulted in a satisfactory outcome. The course of the disease and the persistence of echocardiographic findings with a completely competent aortic valve, suggested us to consider the diagnosis of Lambl’s excrescences. There was no indication for surgical treatment in our patient; so that in the absence of pathological confirmation our diagnostic dilemma was left unresolved. Conclusion. In patients with typical clinical features of IE and filamentous structures on the cardiac valves that are completely competent, Lambl’s excrescences should be kept in mind as a possible differential diagnosis.